Evaluating of the Quality of Hepatic Diffusion Weighted Imaging Using Multiband Imaging With Variable-Rate Selective Excitation. Issue 5 (14th September 2022) - Yoshida, Naofumi; Nakaura, Takeshi; Morita, Kosuke; Yoneyama, Masami; Inoue, Taihei; Tanoue, Shota; Uetani, Hiroyuki; Oda, Seitaro; Nagayama, Yasunori; Kidoh, Masafumi; Hirai, Toshinori
Abstract : Objective: To assess the image quality of diffusion-weighted imaging (DWI) using multiband (MB) imaging with variable-rate selective excitation (VERSE) and compare it to conventional DWI. Methods: We retrospectively evaluated hepatic DWI images of patients (n = 76) according to either the conventional method (SENSE, acceleration factor = 2) (n = 38) or fast scanning method (MB imaging with VERSE, acceleration factor = 2 × 2) (n = 38). We also conducted a volunteer study (n = 15) for those scanning methods. During quantitative analysis, the signal-to-noise ratio (SNR), apparent diffusion coefficient values, and contrast in the liver, spleen, and spinal cord were compared between the 2 groups. During qualitative analysis, all images were independently and blindly evaluated by 2 board-certified radiologists. The image contrast, noise, artifacts, and sharpness were assessed, and the performance of classification was measured using receiver operating characteristic curve analysis. Results: In the retrospective study, the SNRs of the hepatic parenchyma and spinal cord between the 2 protocols were significantly different (liver, 8.9 [interquartile range IQR, 7.6–12.2] vs 13.0 [IQR, 10.0–16.7]; P < 0.001 and spinal cord, 6.0 [IQR, 4.7–9.4] vs 4.3 [IQR, 3.8–6.8]; P < 0.02). No significant differences between the 2 protocols in the other retrospective analyses were noted. In the receiver operating characteristic curve analysis, area under the curve was 0.49 (95% confidence intervals, 0.40–0.58). Conclusion: Multiband VERSE reduced scan time and SNR of hepatic DWI; however, subjective image quality parameters were not significantly impacted.